Caring Across Borders: Demographic Shifts and Migrant Care in ASEAN-Korea Dynamics - Ahmada, Saqib Fardan; Kartiko, Wahid Nur (Jurnal Ilmu Kesejahteraan Sosial, 2025)
This article aims to examine the migration policies and migrant care in the context of relations between ASEAN Member States (AMS) and Korea. As Korea is dealing with an aging population, an increase in female labour force participation, and an ultra low fertility rate, caregiving, especially for the elderly, has become a pivotal issue. Besides, the traditional nuclear family structure, which has historically served as the primary caregiver for the elderly, is also losing its prominence. In such demographic shift, migrant care workers from AMS are filling the demand for caregiving in Korea, leading to a cross-border international migration from AMS to Korea. Departing from this context, this article seeks to address two main questions: How is the condition of migrant care workers from SEA in Korea and how is the current migration regulation regarding this migrant care activities? How can ASEAN and Korea collaborate to advance migration policies and enhance migrant care within the framework of the Comprehensive Strategic Partnership, ensuring the protection and well-being of migrants? The study found that although migrant care workers from AMS could be the supply for the lack of caregiver in Korea, they do not receive wages commensurate with the intensity of their labour. Moreover, caregiving practice is part of the secondary labour market, as described by the dual labour market theory. As Korea continues to grapple with demographic and economic challenges, the role of migrants in the care sector will remain a vital component of its social and policy landscape. Promoting a comprehensive strategic partnership between ASEAN member states and Korea for decent work is essential to ensuring a fair and sustainable care economy.